(untitled) (Journal of the College of Basic Education, 2022)
Eighty Fungal isolates was obtained from the Qualitative screening from the obtained ones, all of which were undergone to fungal quantitative screening to get one isolate. The isolate which was taken from AL-Noor batteries plant (Abu Ghraib), characterized by fast growth on Potato Dextrose agar medium contained the minerals, Fe, Cu, Cd, Pb,Ni,Zn,Cr at concentration of 400 mg/individually. The isolate was identified depending on morphological and cultural properties, also scanning electron microscope was done, it was identified to Aspergillus niger. The isolate showed high growing ability in high temperatures which includes 50 , 55 , 60 c. The maximum concentrations used for the Aspergillus niger isolate was600,800,1000,1200,1400,1600,1800,2000,2200,2400,2600,2800, 3000 for the minerals Fe,Ni,Zn,Cd,Pb,Cr,Cu consequently.